Theory of self-care in the Pregnancy-Puerperal cycle during the Covid-19 pandemic: reflection for nursing practice - Layla Santana Corrêa da Silva; Amanda Marques Bezerra; Ana Paula de Assis Sales; Verusca Soares de Souza; Maria Angélica Marcheti (Universidade de Pernambuco, 2021)
To reflect on self-care in the gravid-puerperal cycle during Covid-19 pandemic in light of Dorothea Orems theory of selfcare. Methods: This is a theoretical-reflexive study focused on bibliographic analysis of literature related to self-care in pregnancy, childbirth and puerperium and the impacts of necessary adaptations to the current pandemic context. Results: The pregnancy-puerperal cycle is a unique moment with adaptations that demand more attention to self-care and require from health professionals strategies that offer information and support to women. With the social isolation in the pandemic, due to the physiological changes of the period, the demands of self-care became fundamental due to the withdrawal of the support network by the new recommendations for prevention of the virus. Conclusions: Orems theory is a strategy to face the pandemic context added to the gravidic-puerperal changes making it possible to provide quality care even amidst so many challenges of the current moment.